Morfološke značilnosti Langerhansovih celic - Štiblar-Martinčič, Draga (Medicinski razgledi, 2000)
Langerhans cells are part of the widely distributed antigen-presenting cells known as dendritic cells with a key role in immune responses. These specialised bone marrow-derived cells were originally found in the epidermis and later demonstrated in the mucosa of other organs. Langerhans cells are difficult to identifiy in sections stained with hematoxylin-eosin. A large number of surface and/or cytoplasmic antigens have been localised on Langerhans cells for immunohistochemical detection. The Birbeck granules are the specific markers of Langerhans cells on electron microscopical level. Langerhans cells represent the primary immune defence of the skin and mucosae with various immunological functions, among which the processing and presenting antigen to T lymphocytes are the most important.
Keywords: Langerhans cells; Langerhansove celice; citologija; Ultrastructure; Immunology; morfologija; Bone marrow; Epidermis; Antigen-presenting cells; T-lymphocytes; Cytoplasmic granules; Microscopy, electron; Hematoxylin; Macrophages